Stabilisation of oil-in-water emulsions with non-chemical modified gelatinised starch - Kasprzak, Miroslaw M.; Macnaughtan, William; Harding, Stephen; Wilde, Peter; Wolf, Bettina (Elsevier, 2018)
In this research, stabilisation of oil-in-water emulsions with non-chemically modified gelatinised starch is presented. Thus far only octenyl succinic anhydride(OSA) modified gelatinised starch has been known to adsorb at emulsion droplet interfaces, acting as emulsifiers. Screening a range of commercially available food starches revealed that a non-waxy rice starch, a waxy rice starch and the waxy maize starch PRIMA600 showed oil-in-water emulsifying ability following gelatinisation. The microstructure of emulsions formulated with 20 % oil and 1 % starch was stable for at least 3 months. Thermal, crystallinity and molecular property analyses as well as amylose and protein content revealed no obvious link to this property. Nevertheless, this research has provided the food industry with exciting results for the formulation of clean label emulsions. Moreover, it presents a concept for oral release food emulsions with destabilisation via salivary amylase digestion of the stabilising starch emulsifier.